Integration of forage legumes into the cropping systems of Nigeria's subhumid zone - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1986)
Summarizes research in crop-forage combinations in subhumid Nigeria w. an aim of developing an integrated pasture-livestock-crop system suitable to accommodate & improve both crop & livestock production.